Prognostic factors influencing survival in small bowel neuroendocrine tumor with liver metastases. Issue 6 (8th August 2019) - Manguso, Nicholas; Nissen, Nicholas; Hendifar, Andrew; Harit, Attiya; Mirocha, James; Friedman, Marc; Lipshutz, H. Gabriel; Amersi, Farin
Abstract: Background: Resection of liver metastasis in small bowel neuroendocrine tumors (SBNET) may improve survival, however, factors influencing prognosis are unclear. We evaluated how the extent of resection influences outcomes. Methods: Patients with SBNET with liver metastasis from 1990 to 2013 who underwent resection of the primary tumor were identified. Outcomes among patients undergoing complete resection (CR), partial resection (PR), or no resection (NR) of liver metastases with resection of the primary tumor only were compared. Results: One hundred eleven patients met the criteria. The median number of liver lesions was seven and median lesions resected was one. Fifty (45%) patients had NR, 41 (36.9%) underwent CR, and 20 (18.1%) underwent PR. The 5‐year overall survival (OS) was 79.4% for NR, 84.7% for PR, and 100% for CR, demonstrating a trend that CR was best, followed by PR then NR ( P  = .02). 10‐year OS showed no significant differences (72.7% NR; 84.7% PR; 82.5% CR; P  = .10). Greater than 10 liver lesions (hazard ratio [HR] 3.6; P  = 0.04) or receiving chemotherapy (HR 3.7; P  = .03) were negative predictors of survival. Conclusion: The extent of resection of liver disease in SBNET influenced survival at 5 years but not at 10 years. In addition, more than 10 liver lesions and chemotherapy were predictors of mortality.